Respiratory insufficiency due to high anterior cervical cord infarction. Issue 3 (1st March 1998) - Howard, R S; Thorpe, J; Barker, R; Revesz, T; Hirsch, N; Miller, D; Williams, A J
Abstract : OBJECTS AND METHODS: Respiratory dysfunction may occur as a result of lesions in the upper cervical spinal cord disturbing the descending pathways subserving automatic and volitional ventilatory control. Four patients are described who presented with acute respiratory insufficiency caused by infarction of the anterior portion of the upper cervical cord due to presumed anterior spinal artery occlusion. RESULTS: Two patients presented after respiratory arrests; they were ventilated and there was no automatic or volitional respiratory effort. Both had signs of an extensive anterior spinal cord lesion at the C2 level and this was confirmed by MRI. One patient presented with a C4 infarction and required ventilation for three months. Ventilatory recovery was characterised by the development of an automatic respiratory pattern. The fourth patient required ventilation for two months after infarction at the C3 level. On attempted weaning he had prolonged periods of hypoventilation and apnoea during inattention and sleep indicating impairment of automatic respiratory control. CONCLUSION: Infarction of the spinal cord at high cervical levels may be due to fibrocartilaginous embolism and involvement of the descending respiratory pathways may occur. Extensive lesions at C1/2 cause complete interruption of descending respiratory control leading to apnoea. Partial lesions at C3/4 cause selective interruption of automatic or voluntary pathways and give rise to characteristic respiratory patterns. The prognosis depends on the level and extent of the lesion.